The SRG rat as a novel host for an orthotopic patient-derived xenograft model of breast cancer brain metastasis - Niveen Fulcher; Hien Nguyen; Andrew Deweyert; Mila Uzelac; Maryam Mozaffari; Qi Zhang; John A. Ronald; John J. Kelly; Ying Xia; Timothy J. Scholl; Fallon K. Noto; Diane Begemann; et al. (Scientific Reports)
Abstract Patient-derived xenograft (PDX) models are essential for understanding the pathophysiology and developing treatment strategies for breast cancer brain metastasis (BCBM). While immunodeficient mouse models allow for human BCBM growth, their small size limits host survival, neurological imaging and therapeutic interventions. This study evaluated the immunodeficient SRG rat (Sprague Dawley Rag2−/−; Il2rg−/−) as a new intermediate-sized host for orthotopic modeling of human BCBM. The primary goal was to determine if the SRG rat brain presents a hospitable environment for orthotopic growth of patient BCBM cells. A secondary goal was to compare phenotypes of the patient and xenografted tumors. Adult SRG rats received stereotactic intracerebral implants of 1 million engineered patient BCBM cells. Bioluminesence imaging (BLI) and magnetic resonance imaging (MRI) provided metabolic and anatomic monitoring of tumor growth. Post-mortem histological analysis compared biomarker profiles in original patient and xenograft tumors. Orthotopic patient-derived BCBM tumors progressed in all SRG rats within 5 weeks post-implantation. BLI radiance increased 125-fold over the study period. MRI revealed tumor-induced brain edema and both patient and xenograft BCBMs exhibited pronounced vascularity and gadolinium enhancement. Histopathology confirmed that xenograft tumors maintained high proliferation indices and biomarker expression consistent with the parent tumor. The SRG rat provided a reliable intermediate-sized host for orthotopic growth of patient-derived BCBM xenografts, offering advantages over existing models for studying tumor behavior and therapeutic responses.